Antibiotic Resistance Profile of Indigenous Streptococcus thermophilus and Lactobacillus bulgaricus Strains Isolated from Traditional Yogurt - Bahareh Moghimi; Maryam Ghobadi Dana; Reza Shapouri; Maryam Jalili (Journal of Food Quality)
Antibiotic resistance signifies a safety hazard to public health. Lactic acid bacteria, particularly, Streptococcus thermophilus and Lactobacillus bulgaricus, are useful organisms responsible for dairy fermentation. In keeping with this, they may transfer antibiotic resistance to human population. We conducted a study exanimated the antibiotic resistance pattern and distribution of antibiotic resistance genes of the S. thermophilus and L. bulgaricus strains isolated from traditional yogurt samples. Fifty-five traditional yogurt samples were collected, and S. thermophilus and L. bulgaricus strains were isolated using the microbial culture. The disk diffusion method in agar wells was utilized to assess the antibiotic resistance pattern of isolates against 13 antibiotic agents. The distribution of antibiotic resistance genes was assessed using conventional PCR. Lactobacillus bulgaricus and S. thermophilus were identified in 94.54% (52/55) and 87.27% (48/55) of yogurt samples, respectively. Both L. bulgaricus and S. thermophilus bacteria were simultaneously identified in 72.72% of samples. Streptococcus thermophilus isolates harbored the highest antibiotic resistance rate against tetracycline (31.25%), ampicillin (31.25%), gentamicin (25%), erythromycin (25%), penicillin (12%), and ciprofloxacin (20.83%). Lactobacillus bulgaricus isolates harbored the highest resistance rate against tetracycline (9.61%), ampicillin (9.61%), gentamicin (9.61%), and erythromycin (7.69%). Streptococcus thermophilus (33.33%) isolates harbored the higher distribution of multidrug resistance than L. bulgaricus (11.53%). aacA-D (20.83%), tetK (16.66%), ermA (14.58%), blaZ (14.58%), and gyrA (12.50%) were the most commonly detected antibiotic resistance genes in S. thermophilus. AacA-D (3.84%) and tet K (3.84%) were the most commonly detected antibiotic resistance genes in L. bulgaricus. Lactobacillus bulgaricus isolates did not harbor tetM, cat1, rpoB, vanA, linA, and strA-strB antibiotic resistance genes. Streptococcus thermophilus and L. bulgaricus strains used in traditional yogurt production can harbor antibiotic resistance genes and subsequently disseminate the resistance to human beings. Monitoring antibiotic resistance in fermented foods should be a common inspection for food quality.